The Effect of Soft Skills and Self Efficacy on Fresh Graduate Job Readiness: Mediation of Work Motivation - Fitriyani, Anissa; Wahyudi, Wahyudi; Kurniasih, Dedeh (Graduate Program Magister Manajemen Pendidikan, 2025)
In times of increasing job competition, the level of job readiness of fresh graduates determines their success in the world of work. Through work motivation, this study aims to examine how self-efficacy and soft skills affect fresh graduate job readiness. This study uses quantitative techniques, causality theory, and questionnaires for data collection using a sample of 160 people and random sampling techniques. As a result, three of the seven hypotheses tested in this study showed a substantial direct effect, while the remaining four were rejected. The novelty of this study lies in analyzing the role of work motivation as a mediating variable on fresh graduate job readiness that has not been widely studied before, and its contribution to helping educational institutions create strategies to develop soft skills and increase self-efficacy so that prospective workers are ready to compete in the labor market.